2019
DOI: 10.1590/1516-4446-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic properties of compounds that counteract oxidative stress, neuroinflammation, and glutamatergic dysfunction: a review

Abstract: Objective:Anxiety disorders are highly prevalent and the efficacy of the available anxiolytic drugs is less than desired. Adverse effects also compromise patient quality of life and adherence to treatment. Accumulating evidence shows that the pathophysiology of anxiety and related disorders is multifactorial, involving oxidative stress, neuroinflammation, and glutamatergic dysfunction. The aim of this review was to evaluate data from animal studies and clinical trials showing the anxiolytic effects of agents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 150 publications
(167 reference statements)
0
19
0
Order By: Relevance
“…Moreover, NAC allowed normal development of retinal blood vessels preventing neovascularization. The protective role of NAC could be explained by acting as a glutathione precursor (cysteine is required for endogenous antioxidant glutathione production), down regulator of the expression of several inflammatory cytokines genes and microglia proliferation inhibitor [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NAC allowed normal development of retinal blood vessels preventing neovascularization. The protective role of NAC could be explained by acting as a glutathione precursor (cysteine is required for endogenous antioxidant glutathione production), down regulator of the expression of several inflammatory cytokines genes and microglia proliferation inhibitor [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, microglial injury may lead to depression, and drugs that inhibit microglial activation, such as minocycline and tumor necrosis factor alpha (TNF-α) inhibitors, are also considered effective antidepressants (Miller and Raison 2015 ; Yirmiya et al 2015 ). In addition, microglia release and respond to several cytokines, including IL-1, IL-6, TNF-a, and IFN-c, which contribute to the maintenance of persistent pain states in autoimmune inflammation of the nervous system (Lee 2020 ; Santos et al 2019 ). In this study, we observed that the upregulation of Iba-1 expression and the release of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in the BLA after CFA injection were decreased by 8-OaS, suggesting that the anxiolytic actions of 8-OaS are linked to the inactivation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that inherently determined anxiety-related behaviors of sP rats are linked also to subnucleus-specific changes in microglia activation. Neuroinflammation and microglia activation are emerging as factors promoting anxiety-related behaviors (see Sild et al, 2017; Stein et al, 2017; Kim and Jeon, 2018; Santos et al, 2018, for recent reviews). However, tissue-resident macrophages (as microglia in the brain) are also thought to constitute the first line of defense that can build up a homeostatic response directed toward repair of neural environment micro-damages in anxiety-related region (Medzhitov, 2008): this led to hypothesize that microglia activation can initially provide a beneficial support to maintain homeostasis in brain, but this error-prone response can be subsequently triggered to enter a chronic, harmful state that can lead to mental state alterations (Wager-Smith and Markou, 2011; Wohleb, 2016).…”
Section: Discussionmentioning
confidence: 99%